Analyzing the trade competitiveness of Indian coconut sector in the liberalization regime - Jayasekhar, S.; Chandran, K.P.; Thamban, C.; Jaganathan, D.; Muralidharan, K. (Journal of Plantation Crops, 2017)
Coconut export sector in India of late gained an outward orientation, especially since the Coconut Development Board was elevated to the status of export promotion council in the year 2009. In the recent period, the growth rate experienced in the coconut based value added products has been stupendous. Since there is an attempt for global value chain up-gradation at the production node of the sector, it is imperative to analyse our strengths in the world market in comparison with the major competitors. We have used the Revealed Comparative Advantage (RCA) methodology to analyse India’s competitiveness in the exports of major coconut value added products traded across the world. The study revealed that, as far as the coconut value added products are concerned, India is comparatively a very small player with paltry export market shares. The analysis of RCA revealed that comparative advantage of India is lower than the major coconut exporting countries like Philippines, Indonesia and Sri Lanka. The Philippines is the dominant player with highest RCA indices in most of the coconut value added product lines. The study suggests the need to formulate plausible strategies to reach the overseas market and capture the optimal share in market segments. Though we have a strong domestic market base, it is an indubitable fact that in the near future due to the evolving trade agreements even in the domestic sector we may confront fierce price competition from the overseas imports. Hence we need to chalk out modalities and execution plans to elevate our export competitiveness and comparative advantage.